PENGEMBANGAN MODEL BISNIS MANISAN CABAI MERAH (Capsicum annum) - Indah Yuliasih dan Nabilah Aisyah (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2015)
ABSTRACT Candied red chilli (Capsicum annum) is one kind of processed vegetable innovation which added by sugar as natural preservative. The objective of research was to generate product profile and determine the best business model design. Based on the result, candied chillihas moisture content of < 15 %, red-colored, sweet and spicy flavor.  Candied red chilli had already met quality standard of dried candied product based SNI 01-3710-1995. The product was packaged using primary packaging by combination of alumunium foil and PP (poly propilene) plastic. Initial business model was assumed based on sweets vegetables business models in Surabaya and sweets business in Bogor city.The business model changed after development of the best product profile and business model development phase such as problem and solution tests. Product profile development phase changed elements of business model such as key partnership, key activities, key resources and cost structure.Business model development phase changed four elements of business model such as customer segment, value propotions, channels and customer relationship. Final result of iteration changed former concept of the product to be more favored by consumers. Keywords: business model, candied, red chilli